THE Penguatan Kompetensi Guru dalam Pengajaran Al-Quran melalui Metode Iqro’ Berbasis Media Kartu dan Praktik Ibadah melalui Metode Demonstrasi Partisipatif di Yayasan Asy-Syifa Banjar: Pengabdian Masyarakat - Pendidikan Agama Islam - Al-Quran dan Ibadah - Abdurrahman, Maman; Nurbayan, Yayan; Tantowi, Yusuf Ali; Nurlatifah, Nurlatifah (Al-Ijtimā': Jurnal Pengabdian Kepada Masyarakat, 2024)
Based on the evaluation of the community service conducted in 2022-2023 in collaboration with the Asy-Syifa Banjar Foundation, it was found that most of the RA and TPA teachers had an ambition to enhance their knowledge and skills, particularly related to teaching Iqro’ and worship practice strategies, especially prayer. Almost all TK/TPA teachers requested the Arabic Language Education Program to help improve their professional quality. Therefore, the goal of this activity was for the TK/TPA teachers under the Asy-Syifa Banjar Foundation to be able to apply the Iqro’ teaching method, particularly through the use of flashcard media, and to implement worship practice strategies, specifically prayer, through the participatory demonstration method. This community service activity focused on teaching Iqro’ through flashcard media and worship practices using the participatory demonstration method. Around 30-40 TK/TPA teachers from Asy-Syifa participated in this activity. The methods used included lectures, practice, simulations, and Q&A sessions. Through this activity, teachers were equipped with various methods for teaching the Quran and strategies for teaching worship practices, especially prayer, using the participatory demonstration method, guided by Arabic language lecturers for the benefit of classroom teaching and learning. The training results showed that TK/TPA teachers understood and were skilled in teaching the Quran using the Iqro’ method with flashcard media and were proficient in teaching prayer using the participatory demonstration method. There were also several significant impacts on student learning outcomes, including: 1) An improvement in students' Quran reading skills through the Iqro’ method based on flashcard media; 2) More interactive and participatory learning; 3) An increase in students' learning motivation; 4) An improvement in social and spiritual skills; and 5) An impact on conceptual understanding and practical application.